Auditory Deficits in Audiovisual Speech Perception in Adult Asperger’s Syndrome: fMRI Study - Tietze, Fabian-Alexander; Hundertmark, Laura; Roy, Mandy; Zerr, Michael; Sinke, Christopher; Wiswede, Daniel; Walter, Martin; Münte, Thomas F.; Szycik, Gregor R. (Frontiers in Psychology, 2019)
Audiovisual (AV) integration deficits have been proposed to underlie difficulties in speech perception in Asperger’s syndrome (AS). It is not known, if the AV deficits are related to alterations in sensory processing at the early level of unisensory processing or at later levels of conjoint multisensory processing. Functional MRI was performed in 16 adult subjects with AS and 16 healthy controls (HC) matched for age, gender and verbal IQ as they were exposed to disyllabic AV congruent and AV incongruent nouns. Simple semantic categorisation task was used to ensure subjects’ attention to the stimuli. The left auditory cortex (BA41) showed stronger activation in HC than AS with no interaction with AV congruency. This suggests alterations in auditory processing in respective unimodal “early” areas as underlying AV speech perception deficits in AS. Whether this is signalling a difficulty in the deployment of attention remains to be demonstrated.